Assessment of Diagnostic clinical reasoning skills among undergraduate Physiotherapy students - Ho, Jason Yi Zeng (2024)
Background: Clinical reasoning is a vital cognitive process in physiotherapy, directly influencing patient outcomes. However, its assessment among Malaysian physiotherapy students has been under-explored. Understanding the diagnostic clinical reasoning skills of these students can provide insights into the effectiveness of current educational strategies and highlight areas for improvement. This study aims to bridge the gap by evaluating the diagnostic clinical reasoning abilities of undergraduate physiotherapy students in a private university, focusing on the integration of theoretical models with practical applications to enhance patient care.